Doors for memory: A searchable database. Issue 11 (1st November 2016) - Baddeley, Alan D.; Hitch, Graham J.; Quinlan, Philip T.; Bowes, Lindsey; Stone, Rob
Abstract : The study of human long-term memory has for over 50 years been dominated by research on words. This is partly due to lack of suitable nonverbal materials. Experience in developing a clinical test suggested that door scenes can provide an ecologically relevant and sensitive alternative to the faces and geometrical figures traditionally used to study visual memory. In pursuing this line of research, we have accumulated over 2000 door scenes providing a database that is categorized on a range of variables including building type, colour, age, condition, glazing, and a range of other physical characteristics. We describe an illustrative study of recognition memory for 100 doors tested by yes/no, two-alternative, or four-alternative forced-choice paradigms. These stimuli, together with the full categorized database, are available through a dedicated website. We suggest that door scenes provide an ecologically relevant and participant-friendly source of material for studying the comparatively neglected field of visual long-term memory.